Effectiveness of a Judo Intervention Programme on the Psychosocial Area in Secondary School Education Students - David Lindell-Postigo; Félix Zurita-Ortega; Eduardo Melguizo-Ibáñez; Gabriel González-Valero; Manuel Ortiz-Franco; José Luis Ubago-Jiménez (Sports, 2023)
Currently, many combat sports are pedagogically conceived as uneducational and unreliable for the development of young people. The present research aims to investigate the influence of a Judo intervention programme on the motivational climate towards sport, aggressive behaviour, emotional intelligence, and self-concept in secondary school students and to establish the relationships between them. This objective was broken down into (a) developing an explanatory model of the variables mentioned above and (b) testing the model equations through a multi-group analysis in terms of pre-test and post-test. The present study conducted a pre–post-test quasi-experimental design with a single experimental group. The sample consisted of a total of 139 adolescents (12.67 ± 1.066), 50.4% of whom were male (n = 70) and 49.6% female (n = 69). The results show that the intervention decreased all types of aggression and increased levels of emotional intelligence. An increase in social, physical and academic self-concept and decreases in the family and emotional areas were also observed. Finally, for the motivational climate, a tendency towards the ego climate to the detriment of the task climate was observed. It is concluded that the Judo intervention programme is effective in decreasing aggressive behaviour and effective in increasing levels of emotional intelligence and self-concept.